Gut morphology of developing Malaysian river catfish Mystus nemurus (Cuvier and Valenciennes) larvae - El Hag, Ghada Ahmed; Kamarudin, Mohd Salleh; Saad, Che Roos; Daud, Siti Khalijah (Marsland Press, 2012)
This study was conducted to monitor ontogenetic changes in the gut morphology of Malaysian river catfish, Mystus nemurus during larval development. Fish larvae were reared in three 1 ton fiberglass tanks. During the study, the larvae were fed on Artemia nauplii at 5 organisms ml feeding-1 from the start of exogenous feeding (4 DAH). The morphological development of the gut in M. nemurus larvae was observed using a profile projector and a light microscope for a 21 days period. At hatching and during the yolk absorption period, the gut was a simple, straight, undifferentiated tube throughout its length. By 4-5 DAH, the gut differentiated to the esophagus, stomach, and intestine which coincided to the commencement of exogenous feeding. Strong (GL = 0.3179TL-0.1412, R2 = 0.9284) relationship was found between gut length (GL) and total length (TL) of fish.